2023
DOI: 10.1007/s12603-023-1951-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Dentition, Use of Dental Prothesis and Oral Health Problems with Frailty, Disability and Diet Quality: Results from Population-Based Studies of Older Adults from the UK and USA

Rachel Kimble,
A.O. Papacosta,
L.T. Lennon
et al.

Abstract: Objectives This study examined the relationships of dental status, use and types of dental prothesis and oral health problems, individually and combined, with diet quality, frailty and disability in two population-based studies of older adults. Design Cross-sectional study. Setting and Participants Men form the British Regional Heart Study (BRHS) (aged 85±4 years in 2018; n=1013) and Men and Women from the Health, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…We used Walker & Avant's concept analysis method to identify antecedents, attributes, consequences and empirical referents of the concept of oral frailty as well as constructing cases. The 8-step analysis includes: (1) selecting the concept; (2) determining the purpose of analysis; (3) identifying all uses of the concept; (4) defining attributes; (5) identifying a model case; (6) identifying borderline, related and contrary cases; (7) identifying antecedents and consequences; and (8) identifying the empirical referents of the defining empirical attributes.…”
Section: Concept Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used Walker & Avant's concept analysis method to identify antecedents, attributes, consequences and empirical referents of the concept of oral frailty as well as constructing cases. The 8-step analysis includes: (1) selecting the concept; (2) determining the purpose of analysis; (3) identifying all uses of the concept; (4) defining attributes; (5) identifying a model case; (6) identifying borderline, related and contrary cases; (7) identifying antecedents and consequences; and (8) identifying the empirical referents of the defining empirical attributes.…”
Section: Concept Analysis Methodsmentioning
confidence: 99%
“…The global population is rapidly aging, and the poor oral health conditions and problems of older adults have become a serious problem that could not be ignored. Studies found that older adults suffered from oral health problems, such as missing teeth, worse oral hygiene, subjective difficulties in eating and swallowing, etc [1]. These oral health problems lead to impaired physical health, cognitive function, decreased social function, reduced series of phenomena and processes that lead to changes in various oral conditions (such as number of teeth, oral hygiene, and oral function) associated with aging and accompanied by decreased interest in oral health, reduced physical and mental reserve capacity, and an increase in oral frailty resulting in eating dysfunction [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation